Analisis Fishbone Diagram Pada Kerusakan Roller Ball Bearing Terhadap Kelancaran Kinerja Ballast Pump No. 2 Dikapal MT. Palu Sipat - Robbi, Shofa Dai; Barbyanavy, Dinda Ayu; Yudianto, Prima Yudha; Gunarti, Monika Retno; Nasri, Nasri (Politeknik Negeri FakFak, 2025)
The ballast pump is one of the important components in the ship's balance system that functions to regulate the volume of ballast water in the ship's tank to maintain the stability and trim of the ship. The ball bearing component plays a role in reducing friction between the pump shaft and the pump housing and ensuring that the shaft remains aligned when the pump is operating. This study aims to determine the causes of ball bearing damage to ballast pumps, the impact caused by the damage, and preventive efforts that can be made. The method used in this research is descriptive qualitative with data analysis techniques using the fishbone method, namely with cause-and-effect diagrams. The results showed that the damage to the ball bearing of the ballast pump was caused by the lack of lubrication and the lack of checking and maintenance. The handling of this problem is done by disassembling the ballast pump and replacing the ball bearing and mechanical seal.